Design of Mini Plants with Self-Watering Features Using Environmentally Friendly Materials (International Journal of Psychosocial Rehabilitation, 2020)
The concern of urban communities towards health continues to increase and can be proven by the growth of health insurance 10-15%, the birth of the Indonesian Gardening community and other healthy lifestyle communities. Air pollution is a major factor causing health problems, because indoor air pollution is 2-5 times (Vidyautami, et al., 2015) worse than outdoors and humans spend 90% of their activities indoors. NASA scientists in the 80s conducted a study of the role of plants in the room to eliminate organic chemicals in the air just by placing air purifier plants in a room with a height of 20cm making a very large reduction for air pollution. But it is not easy to care for these ornamental plants when they are placed in a room. Obstacles to moving ornamental plants from the yard into the room include, in addition to adjusting the types of plants, a pot that can be adjusted to the conditions of the room is also needed. In this design the author aims to be able to make a pot that can adjust to the busyness of the urban community that can facilitate the process of plant maintenance every day.